Ethical Habituation and Pleasure - O'Leary, Paul (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
Is it possible for a person to acquire virtues of character solely by reading books and/or attending lectures on ethical theory? According to Aristotle, no ethical theory, no matter how well formed and powerful, can eliminate the need for a well conducted ethical habituation. One element that allows such an habituation to play a significant role in the acquisition of the virtues is the link between virtue and pleasure. In short, no ethical theory can, on its own, provide a moral education since it cannot generate the experience of pleasure found in one who lives the life of the virtues.